A case report and literature review: Diagnosis of pelvic retroperitoneal angiomyofibroblastoma assisted by next-generation sequencing - Meng, Yue; Shi, Xiaomeng; Zhang, Qianshi (Frontiers in Oncology, 2025)
Angiomyofibroblastoma (AMFB) is a rare benign soft tissue tumor that primarily arises in the vulvovaginal region of women of reproductive age. Due to its rarity, AMFB is often overlooked in the differential diagnosis, and as such, it is not frequently encountered in clinical practice. Here, we present the case of a 29-year-old female with a pelvic retroperitoneal tumor, confirmed postoperatively as AMFB based on histopathological and immunohistochemical findings. Additionally, we highlight the utility of next-generation sequencing (NGS) as a valuable tool in the differential diagnosis of such rare tumors. Due to the tumor was located at the narrow part of the pelvis and was adjacent to important tissues and organs such as the uterus and bladder, we performed surgical resection using the Da Vinci robotic system after obtaining the patient’s informed consent. The procedure was successful, with no complications observed during the three-month postoperative follow-up. Furthermore, we reviewed the literature on AMFB, focusing on reported cases to identify and summarize patient characteristics, clinical presentations, histological features, and diagnostic challenges associated with this rare tumor. We aim to offer a reference for clinicians facing similar cases, aiding in accurate diagnosis and management, while addressing the challenges posed by the rarity and diagnostic complexity of angiomyofibroblastic tumors, ultimately improving clinical outcomes and advancing knowledge.